(untitled) (Homiletic, 2015)
The task of preaching is imbedded in a world that has been shaped by colonialism and imperialism. Preaching in North America will benefit from an engagement with postcolonial theory and a process of decolonization. This process, however, is a significant challenge for white, wealthy western preachers whose own position vis a vis colonialism is somewhat ambiguous. Most preachers in the West are both perpetrators of imperial projects, and simultaneously oppressed by these very systems. Is it possible for such preachers to participate in a process of decolonization? This article argues that it is possible, although preachers must attend to issues such as social location, neocolonizing anticolonialism, and the experiences of those with deeper knowledge of the realities of colonialism. Another key question is the manner in which the proclamation of the gospel is affected by the process of decolonizing preaching. Is a decolonized gospel good news for those who have benefited from colonial and imperial projects? At first, such a gospel may sound like bad news, as it involves a voluntary surrender of power and a willingness to occupy a marginal space. The truly good news is found in the promise of freedom from oppressive systems in which all are caught. Postcolonial preaching problematizes “gospel,” yet ultimately offers both preachers and listeners a way to escape destructive social systems.